Impact of land use cover change on protected natural areas in central region of Sierra Madre Oriental, Mexico - Sahagún-Sánchez, Francisco Javier (Universidad Autónoma de Tamaulipas, 2018)
Land use cover change, resulting from the expansión and extension of human activities, generates negative impact on biodiversity and the provision of ecosystem services, as well as contributing significantly to climate change processes at a regional level. Natural Protected Areas (NPA) represent a public policy instrument to address the trends of change and ecosystem transformation, while allowing the conservation of resources. The objective of this study was to determine the potential impact of the processes involved in land use cover change on the NPA as part of the central region at the Sierra Madre Oriental (SMO) in Mexico by using the special analysis and the scenery simulation of potential change. Satellite imagery was used to determine the changes in natural vegetation cover between 1989, 2000 and 2005 and, using a set of biophysical and socioeconomic variables, a change scenario was simulated for 2025. This study found that the rate of change of vegetation cover at the SMO over the research period was 0.54 % in tropical forests, 0.22 % in forests and 0.23 % in scrublands, while those in NPA were 0.34 % and 0.60 % in tropical forests and forests respectively; 1 578.26 ha of tropical semi-deciduous temperate forest and scrublands were lost from the NPA. If the current land use trends change continues, another 4 542.17 ha are likely to be modified in the future. These results indicate that NPA under study are subject to the pressures of land use change that threaten the natural heritage under protection and that, therefore, management strategies and monitoring need to be redesigned in the short and medium term.